89.1k views
0 votes
Use the quadratic formula to solve. SHOW ALL STEPS FOR FULL CREDIT. Make sure that the final answer has a simplified radical. 2x² -10x +3

User Paha
by
5.3k points

2 Answers

6 votes

Answer:

whats that

Explanation:

User Aubin
by
5.1k points
2 votes

Answer:


x=(5+√(19))/(2)\text{ and } x=(5-√(19))/(2)

Explanation:

If we have the standard form
ax^2+bx+c, then we can use the quadratic formula:


x=(-b\pm√(b^2-4ac))/(2a)

First, let's identify our coefficients. We have
2x^2-10x+3.

This can be rewritten as
(2)x^2+(-10)x+(3).

Therefore, a=2, b=-10, and c=3.

Substitute these values into the quadratic formula. This yields:


x=(-(-10)\pm√((-10)^2-4(2)(3)))/(2(2))

From here, simplify. Evaluate the expression under the square root:


x=(10\pm√(100-24))/(4)

Evaluate:


x=(10\pm√(76))/(4)

Note that:


√(76)=√(4\cdot 19)=√(4)\cdot√(19)=2√(19)

Therefore:


x=(10\pm2√(19))/(4)

We can factor out a 2 from both the numerator and the denominator:


x=(2(5\pm√(19)))/(2(2))

Simplify:


x=(5\pm√(19))/(2)

Therefore, our roots are:


x=(5+√(19))/(2)\text{ and } x=(5-√(19))/(2)

User Calaway
by
5.8k points